The Effect of Solar Panel Use on Household Electricity Cost Savings - Sinuraya, Enda Wista; Triwiyatno, Aris; Winardi, Bambang (Westscience Press, 2026)
This study aims to analyze the effect of solar panel use on household electricity cost savings. The research adopts a quantitative approach involving 160 respondents who are household users of solar panel systems. Data were collected through a structured questionnaire using a Likert scale to measure respondents’ perceptions regarding solar panel utilization and its impact on electricity expenses. The collected data were analyzed using SPSS version 25, including validity testing, reliability testing, descriptive statistics, and simple linear regression analysis. The results show that solar panel use has a positive and significant effect on household electricity cost savings, with a regression coefficient of 0.705 and a significance value of 0.000, which is below the threshold of 0.05. The coefficient of determination indicates that solar panel utilization explains 37.1% of the variation in electricity cost savings, while the remaining percentage is influenced by other factors. The findings suggest that households that adopt solar energy systems tend to experience lower monthly electricity costs due to reduced dependence on conventional electricity supplied by the public power grid. In addition to financial benefits, solar energy also contributes to environmentally sustainable energy consumption. Therefore, the adoption of solar panel technology can be considered a practical solution for improving household energy efficiency and reducing electricity expenditures. The results of this study provide useful insights for policymakers, energy providers, and households in promoting the wider adoption of renewable energy technologies.